American crime story. [videorecording (DVD)] The people v. O. J. Simpson - Travolta, John, 1954-; Gooding, Cuba, Jr., 1968-; Paulson, Sarah, 1974-; Schwimmer, David, 1966-; Greenwood, Bruce, 1956-; Vance, Courtney B.; Toobin, Jeffrey (20th Century Fox Home Entertainment, 2016)
Told from the perspective of the lawyers, it explores the chaotic dealings behind closed doors and how prosecution overconfidence, defense shrewdness and shocking courtroom twists led to one of the most earth-shattering verdicts of all time. It is based on the best-selling book The Run of His Life: The People v. O.J. Simpson by Jeffrey Toobin.